(untitled) (TSUL LEGAL REPORT, 2026)
The article deals with the issues of international cooperation in providing legal assistance in the fight against corruption. In addition, this article is devoted to the interaction of law enforcement agencies in the fight against corruption within the framework of regional international organizations. Moreover, within the framework of this scientific study, proposals were analyzed to improve the system of providing legal assistance in the field of combating corruption. The author’s comparative analysis of international conventions, declarations and legislation of foreign countries served as a reflection of the specifics of this article. Moreover, the relevance of the research topic is because the commission of such crimes is characterized by the use of modern technical means and high-tech facilities of air and land transport, a high transcontinental level of organization and real support from many, including illegal, financial sources. The predicted result of such activities was a significant increase in the number of serious crimes of a transnational nature. The lack of proper legal cooperation between states leads to the emergence and spread of a dangerous practice, when criminals, committing a crime in one state, illegally cross the borders of another to avoid the administration of justice and prosecution. The problem of disclosure, investigation, and prevention of such crimes in the framework of international cooperation in criminal matters is the most relevant today.